Quiet(er) marine protected areas. Issue 1 (15th November 2015) - Williams, Rob; Erbe, Christine; Ashe, Erin; Clark, Christopher W.
Abstract: A core task in endangered species conservation is identifying important habitats and managing human activities to mitigate threats. Many marine organisms, from invertebrates to fish to marine mammals, use acoustic cues to find food, avoid predators, choose mates, and navigate. Ocean noise can affect animal behavior and disrupt trophic linkages. Substantial potential exists for area-based management to reduce exposure of animals to chronic ocean noise. Incorporating noise into spatial planning (e.g., critical habitat designation or marine protected areas) may improve ecological integrity and promote ecological resilience to withstand additional stressors. Previous work identified areas with high ship noise requiring mitigation. This study introduces the concept of "opportunity sites" — important habitats that experience low ship noise. Working with existing patterns in ocean noise and animal distribution will facilitate conservation gains while minimizing societal costs, by identifying opportunities to protect important wildlife habitats that happen to be quiet. Highlights: Anthropogenic ocean noise can harm acoustically sensitive marine organisms. Area-based management can separate wildlife from threats, including ocean noise. Many risk assessments identify sites where marine mammal habitat is noisy. The corollary is "opportunity sites" — key marine mammal habitats that are quiet. Keeping quiet habitats quiet will be easier than making noisy habitats quiet.